2017
DOI: 10.1016/j.neuroscience.2016.12.047
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory EEG activity induced by conditioning stimuli during fear conditioning reflects Salience and Valence of these stimuli more than Expectancy

Abstract: Imaging studies have described hemodynamic activity during fear conditioning protocols with stimulus trains in which a visual conditioned stimulus (CS+) is paired with an aversive unconditioned stimulus (US, painful laser pulse) while another visual stimulus is unpaired (CS−). We now test the hypothesis that CS Event-Related Spectral Perturbations (ERSPs) are related to ratings of CS Expectancy (likelihood of pairing with the US), Valence (unpleasantness) and Salience (ability to capture attention). ERSP windo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 89 publications
5
42
1
Order By: Relevance
“…This was interpreted to reflect evolutionary shaped learning (Hornstein & Eisenberger, 2018;Seligman, 1970). Because oscillatory activity in the theta band affects fear conditioning (Chien, Colloca, Korzeniewska, Cheng, Campbell, Hillis & Lenz, 2017) and because in the present study, touching an attachment figure reduced theta activity, we suggest that reduced fear conditioning as a function of attachment activation is mediated or modulated by reduced theta brain activity. In conclusion, the nature of pair bonding modulates brain activity during partner presence.…”
Section: Discussionsupporting
confidence: 50%
“…This was interpreted to reflect evolutionary shaped learning (Hornstein & Eisenberger, 2018;Seligman, 1970). Because oscillatory activity in the theta band affects fear conditioning (Chien, Colloca, Korzeniewska, Cheng, Campbell, Hillis & Lenz, 2017) and because in the present study, touching an attachment figure reduced theta activity, we suggest that reduced fear conditioning as a function of attachment activation is mediated or modulated by reduced theta brain activity. In conclusion, the nature of pair bonding modulates brain activity during partner presence.…”
Section: Discussionsupporting
confidence: 50%
“…A power increase in gamma power was observed from habituation to the acquisition phase over a broad area in the frontal and occipital electrodes. The authors reported that alpha activity during fear conditioning reflects the salience and valence of conditioned/unconditioned stimuli rather than conditioning [ 33 ].…”
Section: Fear Conditioning Correlatesmentioning
confidence: 99%
“…Neuroimaging studies generally rely on a larger number of participants (N = 20), but include relatively few stimulus repetitions for each of them (e.g., 116 CS± acquisition and extinction trials in (Lithari et al, ), or 40 CS± acquisition trials in (Chien et al, )). Here, we opted for a different approach, including few participants ( N = 5), but increasing the precision of single measurements for each one of them (Meyer, Bonaiuto, et al, ; Troebinger, López, Lutti, Bradbury, et al, ), akin to what used in the field of precision functional mapping (Gordon et al, ) and the nonhuman primate literature (Klavir et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings largely accord with what previous MEG/EEG studies have reported for the sensor level or for cortical areas. In these, CS+ presentations have been shown to result in a decrease in the power of slow oscillations, compared to presentations of CS− (Chien et al, ; Lithari et al, ; Moses et al, ). This pattern of results was replicated in our study, where theta power in the hippocampus and amygdala was significantly lower following presentations of CS+ compared to CS−.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation